(untitled) (CAHIERS MAGELLANES-NS, 2024)
Infertility has been affecting globally, influenced by both men and women factors. Evaluation of female factor and male factor using traditional semen analysis were carried out on the routine basis. In our study findings, we observed males with normal semen analysis report have abnormal readings of DNA fragmentation index (more than 12%).We assessed the DNA integrity using TUNEL assay by measuring the sperm DFI using flow cytometry. Demographic and lifestyle information including age, smoking habit, alcohol consumption, occupational status, educational profile, clothing type and dietary factors were noted. It was observed that smoking, alcohol and non-vegetarian diet were associated with increased values of DNA fragmentation (>12%). Out of total 110 subjects, 51% were having normal values of DFI whereas 49% of the subjects showed high DFI values. Maximum DFI calculated was 42.5%, which was much higher than the threshold value. The major lifestyle factors discussed in the present study are amongst the potential risk factors that could impair the male fertility. Thus, greater awareness and recognition provide better treatment options for those couples seeking conception.